Penerapan Metode Diskusi Untuk Meningkatkan Prestasi Belajar Pendidikan Agama Islam di SMAN 1 Siberut Barat - Nurhayati, Nurhayati (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
In the implementation of learning, there are often issues related to students’ preparedness in engaging with teaching activities, particularly in understanding the learning material. Many students forget or are unaware of the topics to be discussed, which impacts the effectiveness of the learning process. Additionally, insufficient time allocation presents challenges in creating effective and efficient teacher-student interaction. To address these issues, one solution that can be implemented is the use of discussion or assignment methods, either individually or in groups. This method is expected to enhance student participation in the learning process, deepen their understanding of the material, and make the teaching process more interactive. Teachers should not only act as presenters of material but also as facilitators who can engage students in active participation. Through this approach, it is hoped that educational objectives can be optimally achieved